2016
DOI: 10.18632/oncotarget.12308
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-induced synthetic lethality to arginine-starvation therapy by transcriptional suppression of ASS1 is regulated by DEC1, HIF-1α, and c-Myc transcription network and is independent of ASS1 promoter DNA methylation

Abstract: Many human tumors require extracellular arginine (Arg) for growth because the key enzyme for de novo biosynthesis of Arg, argininosuccinate synthetase 1 (ASS1), is silenced. These tumors are sensitive to Arg-starvation therapy using pegylated arginine deiminase (ADI-PEG20) which digests extracellular Arg. Many previous studies reported that ASS1 silencing is due to epigenetic inactivation of ASS1 expression by DNA methylation, and that the demethylation agent 5-aza-deoxycytidine (Aza-dC) can induce ASS1 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 47 publications
4
31
0
Order By: Relevance
“…Although the detailed regulatory mechanisms need to be further investigated, our current results demonstrate that the stead-state levels of p300 and Sin3A are mutually regulated, and while they apparently do not regulate HDAC2 levels, yet HDAC2 levels can influence p300 and Sin3A levels. (iv) Consistent with the negative role of HIF-1α in ASS1 regulation 3 , 17 , 18 , stabilization of HIF-1α (Fig. 3b and c ) suppressed ASS1 expression, whereas downregulation of HIF-1α enhanced ASS1 expression, albeit a minor increase because induction of ASS1 by ADI is a late event (usually takes several hr) (Fig.…”
Section: Resultssupporting
confidence: 74%
“…Although the detailed regulatory mechanisms need to be further investigated, our current results demonstrate that the stead-state levels of p300 and Sin3A are mutually regulated, and while they apparently do not regulate HDAC2 levels, yet HDAC2 levels can influence p300 and Sin3A levels. (iv) Consistent with the negative role of HIF-1α in ASS1 regulation 3 , 17 , 18 , stabilization of HIF-1α (Fig. 3b and c ) suppressed ASS1 expression, whereas downregulation of HIF-1α enhanced ASS1 expression, albeit a minor increase because induction of ASS1 by ADI is a late event (usually takes several hr) (Fig.…”
Section: Resultssupporting
confidence: 74%
“…Silencing DEC1 increased ASS1, lending support to the hypothesis that HIF-1α/c-Myc balance is the dominant mechanism controlling ASS1 expression in many cells [34] . However, this study used cells that lacked significant ASS1 promoter methylation in the untreated state, leaving open the possibility that an unmethylated promoter is required for expression [34] . Performing a similar study in cells that have been shown to silence ASS1 by promoter methylation would be elucidating.…”
Section: Adaptive Resistancesupporting
confidence: 62%
“…Next, we examined the relationship of cell proliferation-regulating proteins with nuclear factor-kappa B (NF-κB), argininosuccinate synthase (ASS1, which is regulated by HIF-1α), and the c-Myc transcription network [ 36 ] or integrin α-5 (ITGA5), which is known to promote the proliferation and inhibit the differentiation of hADSCs [ 37 ]. Our results showed that the expression of ITGA5 mRNA cultured in CDM was about 70% of that of hADSCs cultured in DMEM (10% FBS).…”
Section: Resultsmentioning
confidence: 99%